Горячий снег - Бондарев Юрий Васильевич (Мировая классика, 2004)
Экземпляры: ф.16 (2004) / Инвентарный номер: 48138 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 81 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL